Pre-Exposure Prophylaxis Barriers, Facilitators and Unmet Need Among Rural People Who Inject Drugs: A Qualitative Examination of Syringe Service Program Client Perspectives - Surratt, Hilary L.; Yeager, Hannah J.; Adu, Akosua; González, Evelyn A.; Nelson, Elizabeth O.; Walker, Tamara (Frontiers in Psychiatry, 2022)
Background People who inject drugs (PWID) are at high risk for HIV infection, yet in rural areas PWID are understudied with respect to prevention strategies. Kentucky is notable for heavy rural HIV burden and increasing rates of new HIV diagnoses attributable to injection drug use. Despite high need and the strong evidence for Pre-Exposure Prophylaxis (PrEP) as a gold-standard biomedical HIV prevention tool, scale up has been limited among PWID in Kentucky and elsewhere. This paper explores individual, environmental, and structural barriers and facilitators of PrEP care from the perspective of PWID in rural Kentucky. Methods Data are drawn from an ongoing NIH-funded study designed to adapt and integrate a PrEP initiation intervention for high-risk PWID at point of care in two rural syringe service programs (SSPs) in southeastern Kentucky. As part of this initiative, a qualitative study guided by PRISM (Practical, Robust, Implementation, and Sustainability Model) was undertaken to gather SSP client perspectives on intervention needs related to PrEP, competing needs related to substance use disorder, as well as tangible supports for and barriers to PrEP uptake. Recruitment and interviews were conducted during September-November 2021 with 26 SSP clients, 13 from each of the two SSP sites. A semi-structured guide explored injection behaviors, SSP use, knowledge of PrEP, perceived barriers to PrEP, as well as aspects of the risk environment (e.g., housing instability, community stigma) that may impact PrEP uptake. Interviews were digitally recorded, transcribed verbatim and verified by project staff. A detailed coding scheme was developed and applied by independent coders using NVivo. Coded transcripts were synthesized to identify salient themes in the data using the principles of thematic analysis All study procedures were approved by the University IRB. Results Participants were 96% white, 42% female, with a median age of 41 years (range 21–62); all reported injection use within the past month. Overall, we found low PrEP awareness among this sample, yet interest in PrEP was high, with several indicating PrEP is urgently needed. Clients reported overwhelmingly positive experiences at the SSPs, considering them trusted and safe locations to receive health services, and were enthusiastic about the integration of co-located PrEP services. Lack of basic HIV and PrEP knowledge and health literacy were in evidence, which contributed to common misperceptions about personal risk for HIV. Situational risks related to substance use disorder, particularly in the context of withdrawal symptoms and craving, often lead to heightened HIV injection and sexual risk behaviors. Stigma related to substance use and HIV arose as a concern for PrEP uptake, with several participants reflecting that privacy issues would impact their preferences for education, prescribing and monitoring of PrEP. Noted tangible barriers included inconsistent access to phone service and transportation. Primary supports included high levels of insurance coverage, consistent pharmacy access, and histories with successful medication management for other health conditions. Conclusions Drawing on the critical perspectives of people with substance use disorder, our findings provide important and actionable information on individual and environmental barriers and facilitators of PrEP uptake among rural PWID at high risk for HIV infection. These data will drive the adaptation and implementation of a client-centered approach to integrated PrEP care within rurally located SSP settings to address unmet needs for PrEP care.